Gambling Addiction Defence on Trial: Canadian Expert Witness Perspectives - Simpson, Rob (2014)
The American Psychiatric Association's evolving recognition of pathological gambling as a behavioral addiction (DSM-III, 1980; DSM-V, 2013) has occasioned increased use of the gambling addiction defence in criminal trials. Reflecting upon our experiences as expert witnesses in criminal and civil liability proceedings where gambling addiction was a significant factor, we a) describe the expert witness role; b) examine the links among frequent and intense EGM play, gambling addiction, and financially-based crimes; c) review how revisions to the Diagnostic and Statistical Manual influenced the Canadian judicial system response to such crime; and d) explore prospects for reducing criminal activity by addicted EGM players. We discuss how and why gambling addiction has become generally accepted as a mitigating factor in Canadian criminal trials. In this commentary we also analyze how the plight of addicted gamblers who resort to criminal behavior might be remediated by a) gambling-specific consumer protection measures; b) tighter regulatory control over the addictive elements of EGM play; c) the implementation of gambling courts; and d) a legislated duty of care owed by gambling providers to EGM players